2004
DOI: 10.1074/jbc.m309479200
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ablation of Survivin Uncovers p53-dependent Mitotic Checkpoint Functions and Control of Mitochondrial Apoptosis

Abstract: Survivin is a member of the Inhibitor of Apoptosis gene family that has been implicated in cell division and suppression of apoptosis. Here, we show that preferential ablation of the nuclear pool of survivin by RNA interference produces a mitotic arrest followed by re-entry into the cell cycle and polyploidy. Survivin ablation causes multiple centrosomal defects, aberrant multipolar spindle formation, and chromatin missegregation, and these phenotypes are exacerbated by loss of the cell cycle regulator, p21Waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
3
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 42 publications
(68 reference statements)
8
108
3
2
Order By: Relevance
“…Survivin, a member of the inhibitor of apoptosis protein (IAP) family, has been revealed to participate the control of apoptosis and G 2 /M checkpoint [3,44,45]. It was reported that the expression of survivin was at low level in G 1 and S phase but was elevated in G 2 /M phase, and this G 2 /M specific expression has been related to mitotic spindle checkpoint function [3].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, a member of the inhibitor of apoptosis protein (IAP) family, has been revealed to participate the control of apoptosis and G 2 /M checkpoint [3,44,45]. It was reported that the expression of survivin was at low level in G 1 and S phase but was elevated in G 2 /M phase, and this G 2 /M specific expression has been related to mitotic spindle checkpoint function [3].…”
Section: Discussionmentioning
confidence: 99%
“…In non-small-cell lung cancer cell lines, genetic or pharmacological inhibition of Cox-2 enhances proteosomal degradation of the inhibitor of apoptosis survivin (Beltrami et al, 2004;Krysan et al, 2004a, b). In turn, depletion of survivin causes arrest of DNA synthesis owing to activation of p53 and p21 WafÀ1 (Beltrami et al, 2004;Yang et al, 2004). Thus, in tumor cells with wildtype p53, inhibition of Cox-2 may result in increased p53-dependent growth suppression.…”
Section: Cycloxygenase-2 Inhibitors Tp53 Mutations and Druginduced Amentioning
confidence: 99%
“…It inhibits apoptosis (Altieri, 2001) and is involved in the spindle checkpoint and the regulation of proper chromosomal segregation during mitosis by acting as a member of the chromosomal passenger protein family (Li et al, 1998;Adams et al, 2001). A number of studies have demonstrated that the suppression of survivin results in cells with multipolar mitotic spindles that are either multinucleated or aneuploid (Li et al, 1999;Beltrami et al, 2004;Kappler et al, 2004). Some studies have also indicated that aneuploidy promotes chromosome instability (CIN) in glioma and cervical carcinoma cells (Nitta et al, 2002;Olaharski et al, 2006).…”
mentioning
confidence: 99%